XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, october 18-20, 2018) (Faculty of sport and physical education, University of Niš, 2018)
Faculty of Sport and Physical Education University of Nis in its 47 years long tradition organizes a scientific conference "FIS COMMUNICATIONS". This year we are organizing 21st scientific conference "FIS COMMUNICATIONS 2018". Our profound years long experience in organizing of the conference has contributed to ever increasing high quality of the conference over years. International scientific conference "FIS COMMUNICATIONS 2018" is organized by the Faculty of sport and Physical Education University of Nis under the auspices of the Ministry of Education, Science and Technological Development of the Republic of Serbia. We are proud to announce the key speakers in our plenary sessions as eminent renowned experts in their field of expertise who are coming from the countries taking part in this conference more then once. This conference can boast submission of 70 full text papers. Upon the review process 60 papers were accepted and approved for the publication. Papers are divided into four sessions depending on the topics investigated as follows: Individual and Team Sports, Physical Education, Interdiciplinary and Poster session. Organizers are satisfied with the participation of already renowned researchers and the young, oncoming authors following the thorny path of the scientific investigation, as well. Also a large number of foreign authors and thematic diversity have widen the horizon of the expert and scientific insights, put some new incentive for the cooperation and expression of the new creative efforts. Enclosed you can find the Proceedings of the International scientific conference "FIS COMMUNICATIONS 2018" incorporating all the papers presented at the scientific conference. We would like to express our gratitude to all the participants, especially to the authors of the papers and we expect that all this conference contributes to enhance and further the development of the scientific and expertise thought in the area of sport, physical education and recreation.